Sparse sensing Bridge Weigh-In-Motion for single-span bridges - Agüero Barrantes, Pablo (2025)
In emerging economies, the implementation of Transportation Infrastructure Management is a prevailing need. In order to use limited available resources in the most efficient way, technology emerges as a strategic ally. For the purpose of pavement and bridge preservation, different methodologies have been developed for the detection of overweight vehicles. This article presents the implementation and validation of Bridge Weigh-In-Motion (BWIM) located in Costa Rica through the instrumentation of an in-service highway bridge with minimal instrumentation requirements. The approach used was based on the concept of influence area from strain response time histories. Given the location of the sensors near the bridge abutment to reduce installation requirements, two types of strain responses were analyzed based on horizontal strain and shear strain in order to define quantity and location of sensors for possible implementations. Two calibration trucks were used as reference for calibration and the weight from over 90 trucks were estimated and compared to static measurements from a nearby permanent static weigh station.